Poland's memory wars : essays on illiberalism - Harper, Jo (Journalist) (Central European University Press, 2018)
This volume of essays and interviews by Polish, British, and American academics and journalists provides an overview of current Polish politics for both the informed and nonspecialist reader. The essays approach the questions why and how PiS: Law and Justice, the party of Kaczynski, returned to power and why and how it is doing what it is doing while in power. They help understand and make sense of how ""history"" plays a key role in Polish public life and politics. The language about PiS in Western media tends to rework old stereotypes about Eastern Europe that had lain largely dormant for so.